2016
DOI: 10.1111/jog.13075
|View full text |Cite
|
Sign up to set email alerts
|

Expression of retinoid‐related orphan receptor (ROR)γt on NK22 cells in the peripheral blood and uterine endometrium of women with unexplained recurrent pregnancy loss and unexplained infertility

Abstract: RORγt may be associated with NK22 cells in reproduction. Particularly, higher expression of RORγt may be associated with elevated NK22 cells in uRPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In accordance with the present study, Fuchinoue et al (25) reported that miscarriage and unexplained infertility had a relation with each other and determined that natural killer 22 (NK22) cells were elevated in the peripheral blood and endometrium of women with unexplained infertility and women suffering from recurrent miscarriage. In addition, Ran et al (26) revealed that the core gene of the unexplained infertility and recurrent miscarriage had similar functions such as regulation of immune cells and cellular secretion.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with the present study, Fuchinoue et al (25) reported that miscarriage and unexplained infertility had a relation with each other and determined that natural killer 22 (NK22) cells were elevated in the peripheral blood and endometrium of women with unexplained infertility and women suffering from recurrent miscarriage. In addition, Ran et al (26) revealed that the core gene of the unexplained infertility and recurrent miscarriage had similar functions such as regulation of immune cells and cellular secretion.…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion, we have demonstrated the importance of NKp46 in reproduction. We have reported decreased expression of NKp46 in peripheral blood in women with previous reproductive failures, such as RPL and implantation failure, 16,26,27,34,35 in peritoneal fluid in women with pelvic endometriosis, 36 and in peripheral blood in pregnant women with gestational diabetes mellitus. 37 These studies suggest that regulation of NKp46 expression in various types of NK cells may be one of the key factors in reproductive failure.…”
Section: Discussionmentioning
confidence: 90%
“…Accumulating evidence supports this hypothesis. For instance, it has been shown that women with uRPL have increased endometrial populations of cytotoxic CD16 + uNK [92] and of uNK expressing the natural cytotoxicity receptors NKp46, NKp44, and NKp30 at higher levels than those detected in control women and in women with unexplained infertility or recurrent implantation failure [28,92,134,135]. This suggests that the cytotoxic activity of uNK is higher in RPL than in control women.…”
Section: Unksmentioning
confidence: 99%